Seeking the neural basis of neuropsychiatric symptoms in dementia: neuroimaging findings and controversies - Sone, Daichi; Shinagawa, Shunichiro (Frontiers in Aging Neuroscience, 2025)
The biological basis of neuropsychiatric symptoms (NPS) in individuals who have dementia is poorly understood, despite the significant burden on patients, caregivers, and communities. Recent neuroimaging advances have provided reliable and less-invasive methods to investigate human brains in vivo. However, compared to the significant progress that has been made in the fields of diagnostic values and cognitive symptoms in dementia, the neuroimaging findings of NPS are less consistent, particularly in terms of the affected brain regions. This discrepancy may be due to differences in neuroimaging modalities or analytical methods, the fact that NPS can change over time, and/or the subjective nature of NPS assessments. In this narrative review, we summarize the extant literature on neuroimaging findings of NPS in dementia. We also discuss both the controversies and potential solutions to overcome the current problems.